interstitial deletion of 15q22q23 with global developmental delay and hypotonia: the first Korean case - Ha-Su Kim; Jin-Yeong Han; Myo-Jing Kim (Korean Pediatric Society, 2015)
Interstitial deletions involving the chromosome band 15q22q24 are very rare and only nine cases have been previously reported. Here, we report on a 12-day-old patient with a de novo 15q22q23 interstitial deletion. He was born by elective cesarean section with a birth weight of 3,120 g at 41.3-week gestation. He presented with hypotonia, sensory and neural hearing loss, dysmorphism with frontal bossing, flat nasal bridge, microretrognathia with normal palate and uvula, thin upper lip in an inverted V-shape, a midline sacral dimple, severe calcanovalgus at admission, and severe global developmental delay at 18 months of age. Fluorescence in situ hybridization findings confirmed that the deleted regions contained at least 15q22. The chromosome analysis revealed a karyotype of 46,XY,del(15) (q22q23). Parental chromosome analysis was performed and results were normal. After reviewing the limited literature on interstitial 15q deletions, we believe that the presented case is the first description of mapping of an interstitial deletion involving the chromosome 15q22q23 segment in Korea. This report adds to the knowledge of the clinical phenotype associated with the 15q22q23 deletion.